Bibliotecas dos Institutos Federais de Educação, Ciência e Tecnologia: uma avaliação de suas condições de funcionamento - Samuel Goncalves Proenca (2018)
The Federal Institutes of Education, Science and Technology, were created by law nº 11,892 of 2008 and are institutions of higher education, basic and professional. This study evaluates four libraries Federal Institute, the Federal Institute of Goiás (IFG), the Federal Institute of Santa Catarina (IFSC), the Federal Institute of São Paulo (IFSP) and the Federal Institute of Ceará (IFCE) to know its operating conditions. Its objective is to evaluate and understand the mixed libraries, school and university, of the Institutes as to their functioning, human, physical, material and informational resources, besides the services and products offered to generate subsidies for a better management of libraries in Brazil. The population was constituted of 102 libraries of all the campuses of the four institutes, and to obtain the data we opted for the use of questionnaire via Internet. In addition to the application of a questionnaire to obtain the information, documents available on the websites of these institutions and on the transparency portal of the federal government were consulted. From the consolidated parameters for school libraries and university libraries a parameters was created for the evaluation of mixed libraries. The questionnaire was applied and a return rate of electronic questionnaires of 64% was obtained. The services that are most offered at the institutes are book lending (98%) and local consultation (98%) and the least offered are loan between libraries (21%) and bibliographic switching (15%). IFG and IFSC have a fully computerized collection catalog and IFG has the highest number of books per student, in total there are 15 books per student. In the IFSP, 95% of libraries own and practice collections development policy, IFSC 86%, IFG 50% and IFCE only 47%. More than 85% of the libraries have free access to the Internet and have a wireless network. The data show that libraries need improvement, many have few professionals, some do not even have a librarian, do not have a fully computerized catalog of the collection, have few books and computers to study.